Efeito da composição genética nas características de termorregulação em vacas Girolando em Tapira, MG - Cruz, Patrícia Ferreira Fernandes da (2015)
The aim of this study was to evaluate physiological parameters and morphologic characteristics of the haircoat, and thermic gradients of crossbred cows Holstein-Gir in the Tapira municipal, MG. 49 cows in lactation were used from six Holstein (H) and Gyr (G) genetic groups 1/4, 3/8, 1/2, 5/8, 3/4 and 7/8 were distributed in delineation throughout the study. The dry-bulb temperature and relative humidity were recorded, and the temperature and humidity index (THI) was calculated. The rectal temperature, respiratory rate and body surface temperature were measured, as were hair thickness, numbers, length and angle. Cows of a larger proportion of the Holstein cattle (5/8, 3/4 e 7/8 HG) demonstrated a longer respiratory frequency of the upper hair in comparison to the animals with a genetic composition closer to Zebu (1/2, 3/8 e 1/4 HG). Animals from the 1/2 and 1/4 HG genetic groups showed the greatest hair angle (P<0.05). The rectal temperature, hair coat thickness and number of hairs of 1/4, 3/8, 1/2, 5/8, 3/4 and 7/8 Holstein-Gyr cows were similar and within the normal range for dairy cattle.